1999
DOI: 10.1091/mbc.10.1.211
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Analysis of Transcription and Splicing in the Cell Nucleus after Bromo-UTP Microinjection

Abstract: In this study we demonstrate, at an ultrastructural level, the in situ distribution of heterogeneous nuclear RNA transcription sites after microinjection of 5-bromo-UTP (BrUTP) into the cytoplasm of living cells and subsequent postembedding immunoelectron microscopic visualization after different labeling periods. Moreover, immunocytochemical localization of several pre-mRNA transcription and processing factors has been carried out in the same cells. This high-resolution approach allowed us to reveal perichrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
198
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(220 citation statements)
references
References 61 publications
19
198
0
3
Order By: Relevance
“…Together, these results show that both the diffuse nucleoplasmic staining and the overlap of CF I m staining with the periphery of nuclear speckles reflect CF I m association with sites of ongoing transcription and with pre-mRNA molecules. These results confirm and extend previous ultrastructural observations and support the idea that not only splicing (Cmarko et al, 1999;Lamond and Spector, 2003) but also 3Ј end processing of pre-mRNAs may occur on PFs.…”
Section: Molecular Biology Of the Cell 1286supporting
confidence: 91%
See 3 more Smart Citations
“…Together, these results show that both the diffuse nucleoplasmic staining and the overlap of CF I m staining with the periphery of nuclear speckles reflect CF I m association with sites of ongoing transcription and with pre-mRNA molecules. These results confirm and extend previous ultrastructural observations and support the idea that not only splicing (Cmarko et al, 1999;Lamond and Spector, 2003) but also 3Ј end processing of pre-mRNAs may occur on PFs.…”
Section: Molecular Biology Of the Cell 1286supporting
confidence: 91%
“…Together, these results show that both the diffuse nucleoplasmic staining and the overlap of CF I m staining with the periphery of nuclear speckles reflect CF I m association with sites of ongoing transcription and with pre-mRNA molecules. These results confirm and extend previous ultrastructural observations and support the idea that not only splicing (Cmarko et al, 1999;Lamond and Spector, 2003) but also 3Ј end processing of pre-mRNAs may occur on PFs.In addition, our data suggest that paraspeckles observed by immunofluorescence may correspond to IGAZs. To clar- ify this point, we examined by immunoelectron microscopy the localization pattern of PSF, a protein that was recently localized to paraspeckles (Fox et al, 2005).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…This work describes a nonisotopic method for investigating the kinetics of RNAs in cells at light and electron microscopic levels+ Surprisingly, previous studies suggest that BrUTP is poorly incorporated into RNA and that the presence of bromine inhibits its transport and/or processing+ For instance, microinjection of high concentrations of BrUTP into living cells has been proved to be toxic and prevents transport to the cytoplasm (Fay et al+, 1997), and complete substitution of uridine inhibited splicing and translation in vitro (Sierakowska et al+, 1989;Schmittgen et al+, 1994;Wansink et al+, 1994)+ However, in these previous studies, the introduction of nucleotide analogs was generally achieved by cell membrane permeabilization using Triton X-100 (Dundr & Raska, 1993;Jackson et al+, 1993;Wansink et al+, 1993;Hozak et al+, 1994;Masson et al+, 1996;Melcak et al+, 1996) or by microinjection (Wansink et al+, 1993;Masson et al+, 1996;Cmarko et al+, 1999)+ Consequently, these procedures could greatly affect the cell integrity+ Moreover, the permeabilization treatment may cause drastic alteration and partial degradation of subcellular structures+ In contrast, it has been shown recently that when cells are exposed for short periods of time to low concentrations of the nucleoside analog BrU, instead of the nucleotide analog BrUTP, they grow normally and the resulting BrRNAs are transported to the cytoplasm (Iborra et al+, 1998)+ However, this labeling only revealed nonnucleolar RNAs+…”
Section: The Approach For Identifying Both Transcription and Processimentioning
confidence: 99%